(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
In this paper, we have suggested a generalized estimator for the estimation of product of population means in the presence of measurement errors. The expression of bias and mean square error are derived under measurement errors model. Further, we have also proposed a jack-knife version of the estimators based on Quenouille’s method in presence of measurement errors. Finally, some concluding remarks are made clearly demonstrating the importance of the proposed classes.